Evaluation of anal cytology and human papillomavirus infection in high-risk women: a cross-sectional study (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Anal cancer incidence has been on the rise over the past few decades. This study aimed to assess anal Papanicolaou (Pap) smear changes in women with high risk for dysplasia and human papillomavirus (HPV) infection. METHODS This cross-sectional study was conducted on 121 patients referred to the Gynecology Oncology Clinic of Imam Hossein Medical Center between 2020 and 2021 in Tehran, Iran, who had cervical and vulvar dysplasia, cervical HPV infection, and abnormal cervical cytology results and were over 21 years old. Data analysis was performed using SPSS software version 21 (IBM Corp., USA) at a significance level of 0.05. RESULTS 121 women, with a mean age of 39.69 years, were included in this study. Overall, 23.1% of women had positive anal HPV results, and 35.5% were over 40 years old. Younger age was associated with an increased risk of anal HPV (p = 0.045). 33.9% of women were single and had a higher risk of anal HPV. Multiple sexual partnerships and anal sex were the significant risk factors for anal cancer (p<0.001). Women with positive anal HPV results had significantly more genital warts (p<0.001). No significant difference was observed in smoking, educational level, and cervical Pap smear results between women with negative and positive rectal HPV results. CONCLUSIONS Younger age at diagnosis, being single, having multiple sexual partnerships, having anal sex, and having genital warts were associated with anal HPV infection in women. Abnormal anal cytology was only associated with being single and having multiple sexual partners.